The Buruli Ulcer. (September 2015) - Kumar, Satendra; Basu, Somprakas; Bhartiya, Satyanam Kumar; Shukla, Vijay Kumar
Buruli ulcer (BU) is caused by Mycobacterium ulcerans and can manifest as a simple nodule or as aggressive skin ulcers leading to debilitating osteoarthritis or limb deformity. The disease is more prevalent in those living in remote rural areas, especially in children younger than 15 years. The exact mode of transmission is possibly through traumatic skin lesions contaminated by M ulcerans . IS2404 polymerase chain reaction from ulcer swabs or biopsies is a rapid method for confirmation of BU. In coendemic countries, HIV infection complicates the progression of BU, leading to rapidly spreading osteomyelitis. Treatment is principally medical, with antitubercular drugs, and surgery is utilized for complicated disease. Because of ineffective vaccination, primary prevention is the best option for control of the disease.